Pengaruh Persepsi Harga dan Promosi terhadap Pembelian Kompulsif pada Pengguna Marketplace di Kota Semarang - Firdaus, Nafiatul Faiza; Santoso, Agus Budi (https://jurnal.binamandiri.ac.id/, 2023)
A marketplace is a means of conducting shopping activities. Its presence brings convenience and encourages consumptive behavior that is difficult to control, such as compulsive buying. This study aims to analyze the influence of compulsive buying seen from the perception of price and promotion. Through questionnaires distributed to 100 respondents and using descriptive analysis methods and multiple linear regression analysis, the results showed that the price perception variable did not affect compulsive buying, but the promotion variable influenced compulsive buying.